How to find the answer for 4sqrtx(2sqrtx+3sqrt7) and simplify it too?

1 Answer
Sep 26, 2017

8x+12sqrt7sqrtx

Explanation:

First, we distribute parentheses/brackets using: x(y+z)=xy+xz

Therefore,
4sqrtx(2sqrtx+3sqrt7) is the same as 4sqrtx*2sqrtx+4sqrtx*3sqrt7

4sqrtx*2sqrtx=8x because sqrtx*sqrtx=x
So, you can just multiply the numbers: 4*2=8 and add the x.

For 4sqrtx*3sqrt7, you take 4*3=12 and you combine sqrtx and sqrt7 together.
So, the equation on the right side would be 12sqrt7sqrtx.

Add both parts together:
8x+12sqrt7sqrtx